Integrating GWAS, linkage mapping and gene expression analyses reveal the genetic control of first branch height in Brassica napus L - Dong, Zhixue; Tang, Minqiang; Cui, Xiaobo; Zhao, Chuanji; Tong, Chaobo; Liu, Yueying; Xiang, Yang; Li, Zaiyun; Huang, Junyan; Cheng, Xiaohui; Liu, Shengyi (Frontiers in Plant Science, 2022)
Rapeseed (Brassica napus L.) is a crucial oil crop cultivated worldwide. First branch height, an essential component of rapeseed plant architecture, has an important effect on yield and mechanized harvesting; however, the underlying genetic mechanism remains unclear. In this study, based on the 60K single nucleotide polymorphism array and a recombinant inbred lines population derived from M083 and 888-5, a total of 19 QTLs were detected in five environments, distributed on linkage groups A02, A09, A10, C06, and C07, which explained phenotypic variation ranging from 4.87 to 29.87%. Furthermore, 26 significant SNPs were discovered on Chr.A02 by genome-wide association study in a diversity panel of 324 re-sequencing accessions. The major QTL of the first branch height trait was co-located on Chr.A02 by integrating linkage mapping and association mapping. Eleven candidate genes were screened via allelic variation analysis, inter-subgenomic synteny analysis, and differential expression of genes in parental shoot apical meristem tissues. Among these genes, BnaA02g13010D, which encodes a TCP transcription factor, was confirmed as the target gene according to gene function annotation, haplotype analysis, and full-length gene sequencing, which revealed that TATA insertion/deletion in the promoter region was closely linked to significantly phenotypic differences BnaA02.TCP1M083 overexpression resulted in decreased branch height and increased branch number in Arabidopsis. These results provide a genetic basis for first branch height and the ideal architecture of B. napus.